Putusan MK Yang Bersifat Positif Legislature - Pane, Ramadhan Siddik; Kurniawan, Puji (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The Constitutional Court in the case of testing the constitutionality of an Act is declared granted, then by the provisions of the laws and regulations only given the authority to declare the material content of paragraphs, Articles, and / or parts of the Law contrary to the 1945 Constitution and has no binding legal force. Or make the process of making laws contrary to the mechanism of formation that has been regulated by the laws and regulations (negative legislature). However, in some cases the Constitutional Court in its ruling included new legal norms (positive legislatures) that are considered to have entered the realm of legislative authority. So based on this there is an increase in the authority of the Constitutional Court from negative legislature to positive legislature. Based on the picture of the problem, researchers want to further know how the constitutional court's authority in issuing positive legislature decisions, then what consideration factors are used by constitutional court judges in issuing positive legislature rulings. This research is assembled based on the type of juridical normative research by utilizing the legal approach and the case approach. The theory used in solving the above problems is to use progressive legal theory and positive legal theory. So that with the data obtained from the results of case review and law, it is processed by reducing data and cases. The results of this study state that the Constitutional Court in the case of testing the constitutionality of the Law based on norms stipulated in the laws and regulations only as a norm-spinning or negative legislature. However, based on the knife analysis of the progressive legal theory, the authority can become a new norm maker with various rules included in the sound of the verdict or positive legislature. The factor considered by constitutional court judges in stringing together the ruling is substantive justice considerations based on progressive theory, then this is supported by the purpose of the establishment of law in Islam is to realize justice.